Climate change impacts and adaptation in Nepal - Bartlett, R.; Bharati, Luna; Pant, Dhruba; Hosterman, H.R.; McCornick, Peter G. (International Water Management Institute, 2010)
The impact of climate change (CC) on water resources is likely to affect agricultural systems and food security. This is especially true for Nepal, a least developed country, where a high percentage of the population is dependent on agriculture for its livelihoods. It is thus crucial for Nepal?s leaders and resource managers to draft and begin implementing national adaptation plans. This working paper aims to create a more comprehensive understanding of how the impacts of CC will be realized at different scales in Nepal, from household livelihoods to national food security, and the many institutions governing the ultimate adaptation process.